Snow Balling and Brainstorming Method In Pregnant Mother Classes - Mardeyanti Mardeyanti; Siti Masitoh (Poltekkes Kemenkes Jakarta III, 2021)
During pregnancy, there are system changes that require adaptation, both physiological and psychological. With these changes, pregnant women must know and understand what they are experiencing, so they need health education during pregnancy and how to prepare for safe delivery. Mother class is a means of learning together about pregnant women's health, increasing knowledge, change attitudes and mothers' behavior. The purpose of this study was to determine the differences in health education with snowballing and brainstorming methods in pregnant women in the class to increase knowledge and attitudes about preparation for pregnancy and childbirth. This study's design was Quasi-experimental with a pretest-posttest design of two snowballing groups and a brainstorming group. The number of samples for each group of 30 pregnant women. Analysis with Chi-Square and T-Test. The study results showed significant differences in knowledge and attitudes on the snowballing method (p-value of 0.000) and the brainstorming method with a p-value of knowledge of 0.011 and attitude of 0.000. Health education using snowballing has a more substantial effect, especially on the attitudes of pregnant women.